The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/onco.13639
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of the FoundationOne CDx Assay to Therapeutic Decision-Making for Patients with Advanced Solid Tumors

Abstract: Background Implementation of personalized medicine requires the accessibility of tumor molecular profiling in order to allow prioritization of appropriate targeted therapies for individual patients. Our aim was to study the role of comprehensive genomic profiling assays that may inform treatment recommendations for patients with solid tumors. Materials and Methods We performed a prospective study to evaluate the feasibility of application of the FoundationOne CDx panel—which detects substitutions, insertions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
34
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 20 publications
(22 reference statements)
11
34
1
2
Order By: Relevance
“…In our study, the most common mutation was also TP53 (47%), but the second most common mutation identified in our study was CDKN2A (29%). Our study showed a median age of patients to be 56 years, which is similar to a study on hematological cancers sent for comprehensive genetic profiling, whom had a mean age of 54 years ( 10 ) but slightly dissimilar to the median age of 62 years found in patients with advanced solid tumors sent for FoundationOne CDx panel ( 18 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, the most common mutation was also TP53 (47%), but the second most common mutation identified in our study was CDKN2A (29%). Our study showed a median age of patients to be 56 years, which is similar to a study on hematological cancers sent for comprehensive genetic profiling, whom had a mean age of 54 years ( 10 ) but slightly dissimilar to the median age of 62 years found in patients with advanced solid tumors sent for FoundationOne CDx panel ( 18 ).…”
Section: Discussionsupporting
confidence: 81%
“…A study on rare and refractory cancers, found that the most common mutations identified were TP53 (46%), followed by RAS/RAF/APK(45%) ( 8 ). A study on advanced solid tumors using FoundationOne CDx panel found TP53 (65%) followed by PIK3CA (19%) were the most common mutation identified ( 18 ). A final study using FoundationOne CDx testing found the most common mutations identified were KRAS (94%) followed by TP53 (76%) ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though there are some differences across different panels in terms of the number of genes included and genetic alterations evaluated, they all include well-known high-penetrance genes, as well as moderate-and low-penetrance genes and variants of unknown significance (VUS) [19]. The only two panels approved by FDA as companion diagnostic for solid tumors are FoundationOne CDx (324 genes) [20] and MSK-IMPACT (468 genes) [21], which are performed in CLIA (Clinical Laboratory Improvement Amendments)-certified laboratories. Nonetheless, there are many targeted panels that clinicians can order from certified facilities like Caris Life Science (592 genes) by Caris Molecular Intelligence, as well as commercially available panels to test in research laboratories like Thermo Fisher's Oncomine Cancer Gene Mutation Panel v2 assay (143 genes), Oncomine Comprehensive Panel_v3 DNA (161 Genes), Oncomine Focus Assay DNA (52 Genes), Illumina's TruSight Oncology 500 (523 genes), TruSight Tumor 170 (170 genes), and QIAGEN's QIAseq Targeted DNA Panels just to name some of the most commonly advertised.…”
Section: Ngs Available Platforms For Multi-gene Testingmentioning
confidence: 99%
“…Recent developments in DNA extraction methods and optimisation improve assay performance [42,43]. In fact NGS solutions have been achieving regulatory approval such like Oncomine Dx (ThermoFisher Scientific) for targeted therapies in non-small cell lung carcinoma (NSCLC) [44]; Praxis (Illumina) characterising 56 KRAS/NRAS mutations for colorectal cancer companion diagnostics (CDx); Memorial Sloan Kettering-Integrated Mutation Profiling of Actionable Cancer Targets (MSK-IMPACT), the first U.S. Food & Drug Administration (FDA) approved tissue profiling test that detecting aberrations across 341 cancer genes for solid cancer tissue diagnostics but not prescriptive for any specific therapeutic product [45]; and FoundationOne CDx which is the first FDA-approved broad CDx test that is clinically and analytically validated for all solid tumours for therapeutic indication and has a success rate of >95% on FFPE [46].…”
Section: Molecular Pathology: Overcoming Challenges For Solid and Liqmentioning
confidence: 99%